(3eYQaI GdfSGc aj eYQaI GdShGcs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdYXje CeG HYO ajbhd Cf gPg QSGdI fGaYI ddfSGc ai eYQaI aVjdI GdESJjGc s
(3BNQgG (B:s
(3hefgG QhGg eSde ai UMjMI ef MOjK CHj SYjO GdNOQi Cf QShd Gddg Udi Gddg Ydjg hSde bGd ZSd GdLeYI Ydi cd eMJde hShGc hjeS ef GdWjH eG bOQ Ydjg Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs